Comprehensive genotyping reveals novel CFTR variants in cystic fibrosis patients from the Russian Federation. Issue 3 (12th December 2018) - Petrova, Nika V.; Marakhonov, Andrey V.; Vasilyeva, Tatiana A.; Kashirskaya, Natalya Y.; Ginter, Evgeny K.; Kutsev, Sergey I.; Zinchenko, Rena A.
Abstract : Single nucleotide variants are represented as lines. The height of the line corresponds to the allele frequency. Gross chromosomal copy number variations are shown as arrows. Color corresponds to the mutation type. Complex alleles represented with a clip. Previously reported variants are located above the schematic gene representation. Their names are presented in Table 1 in main text. Novel variants are depicted beneath the schematic gene representation.